Risk Factor Stratification in Patient with Recurrent Stroke in Bangladesh - Ahmed, Faruk; Hoda, Md Durul; Rashid, Md Abdur; Badiuzzaman, Md; Hossain, Amir; Refatul Islam, Mohammad; Hossain, Md Emran (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Stroke is a non communicable disease of increasing importance. Stroke is a major cause of death and disability in the world. Individual who suffered from stroke are at high risk of suffering recurrent stroke. So it is important to establish the risk factor for secondary prevention. The aim of this study is to find out the association of risk factor of recurrent stroke and it helps to take steps to reduce recurrent stroke. Materials and methods: This is a cross sectional observational case control study was conducted at Dhaka Medical College Hospital during 1st January to 31 December 2011. Definition was followed by WHO stroke manual. Results: In this study two leading risk factors were found hypertension and smoking respectively 78% and 72%. Among risk factors others were diabetes 56%, dyslipidemia 24%, cardiac diseases (AF, IHD, Valvular heart disease) 22%, Mean age of patient 61.09. Ischemic stroke found in 68% and haemorrhagic in 32% of patient. Conclusion: The common risk factors of stroke are also attributed to risk factor of stroke. Noncompliance to drug and life style modification also important cause of recurrent stroke. JCMCTA 2022 ; 33 (1) : 93-96